The forests and related vegetation of Kwerba, on the Foja Foothills, Mamberamo, Papua (Indonesian New Guinea) - Heist, M. van; Sheil, Douglas; Rachman, I.; Gusbager, P.; Raweyai, C. O.; Yoteni, H. S. M. (2010)
We describe the vegetation of Kwerba, in the foothills of the Foja Mountains in the Mamberamo Basin of West Papua, Indonesia. Few surveys have been carried out in this remote area of Western New Guinea. Working in collaboration with local people we made 15 plots, 10 in primary forest, 3 in secondary forest and 2 in gardens. A total of 487 morpho-species were distinguished, of which 32 % (156) did not match any herbarium specimens or published reference. Tree densities (598 +/- 136/ha) are similar to lowland forests elsewhere, but mean stem sizes (22 +/- 1 cm dbh and 21 +/- 2 m height for trees over 10 cm dbh) appear small. Numbers of tree species per plot (22 +/- 4, of 40 stems recorded) are unremarkable, but levels of endemism are potentially high with many of the unidentified species being rare (seldom collected) or undescribed. This is the first quantitative description of vegetation in Kwerba, Foja and Mamberamo, and joins only a handful of such studies in Papua. Additional botanical and ecological survey effort is greatly needed in Mamberamo, and in New Guinea generally.